The Student Practitioner in the Early Childhood Studies / An Essential Guide to Working with Children - Hey Christine; Oates Ruby (Rouledge, 2014)
Introduction, The Student Practitioner, The Student as Researcher, The Emerging Practitioner, The Developing Practitioner, The Enabling Practitioner, The Critically Reflective Practitioner, The Student Practitioner Constructing a Professional Identity, The Student Practitioner as Future Leader, Index.